Sebuah PENCARIAN FILE JURNAL DENGAN QUERY KATA PADA LIST KUMPULAN DOKUMEN JURNAL MENGGUNAKAN METODE VECTOR SPACE MODEL - Khatami, Maula (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2020)
Journals are articles about research that are very useful among academics and students alike. Every time we learn a new knowledge, we certainly need a guide that is verified and also credible. Students and academics were greatly helped by this journal. With journals help students and academics get references from previous research and get more insights so that they are able to make a related research and can even be improved from previous research. However, there are still many students and academics who find it difficult to find the right journal for their needs. So here the authors make a research system of information retrieval about journal searches by querying words using the vector space model method. In the suffix tree clustering method and the Vector Space Model, each document and keyword that has been carried out by the Text Mining process is then given the weight of each word contained in each existing document with the Term Frequency - Inverse Document Frequency (TF-IDF) weighting algorithm.